The Economic Effects of Direct and Indirect Employee Involvement: Evidence From Corporate Social Responsibility Reports of Chinese Listed Companies - Jiang, Yongzhong; He, Xixi; Zhu, Yutao; Wu, Guosong; Gao, Xinzhi (Frontiers in Psychology, 2021)
Employee direct involvement and indirect involvement have been identified as essential forms of an enterprise’s democratic management in the digital economy. Research on the complementary effects of direct and indirect involvement is still in a blank state in China, which limits the external validity and accumulation of employee participation theory.The present study aimed to investigate the complementary effects of employee direct involvement and indirect involvement on the firm’s financial performance.Although previous research suggests that the influence of employee direct or indirect involvement on corporate financial performance has been examined separately, it is unclear whether the association between employee direct involvement and indirect involvement is complementary or conflictual. Based on strategic human resource management theory, we semantically encode 2 680 corporate social responsibility reports and the annual reports of 268 state-owned listed enterprises published from 2014 to 2018 via content analysis method, and the economic effects of employee direct involvement and indirect involvement were concurrently measured. we use configuration theory to explore the complementary effects between employee direct involvement and indirect involvement.Our results reveal that (1) employee involvement in Chinese enterprises was unbalanced, (2) both employee direct involvement and indirect involvement were positively related to enterprise’s financial performance, and (3) there is a complementary effect between the two forms of employee involvement. Theoretical and practical implications of these findings are discussed.